Supratentorial infarcts accompanying hiccup - Ryo Itabashi; Kaoru Endo; Takuya Saito; Kazuki Fukuma; Yukako Yazawa (Brain and Behavior, 2019)
Abstract Backgrounds The main culprit lesion causing hiccup in patients with ischemic stroke is thought to involve the medulla oblongata, but some cases of hiccups caused by damage to the supratentorial cortex have been reported. The present study aimed to address the clinical and radiological characteristics of acute stroke patients accompanied by hiccups caused by supratentorial lesions. Method We retrospectively studied 5,309 consecutive patients with acute ischemic stroke or transient ischemic attack who were admitted to our institute within 7 days after onset between April 2006 and September 2017. We searched for the term “hiccup” in prospectively collected descriptive datasets and analyzed associations between hiccup and clinical and radiological findings, with particular focus on patients with supratentorial lesions. Results We finally selected 16 stroke patients accompanied by hiccup. Nine patients had infarcts in the lateral medulla oblongata, and others had supratentorial infarcts (three patients with cortical infarcts, four patients with subcortical infarcts). Moreover, the right hemisphere was frequently damaged in this series (6/7, 86%). Conclusions Hiccup could be caused by supratentorial infarcts including the insular cortex, temporal lobe, and subcortex.